Non-minimum phase output reference trajectory tracking based on second-order sliding mode control for a VTOL aircraft. (15th April 2011) - Tang, Zhili; Lei, Humin; Shao, Lei; Li, Jiong; , Zun Yang
In this paper, a robust dynamic feedback controller is developed to force a non-minimum phase, underactuated vertical take-off and landing (VTOL) aircraft to track a reference trajectory generated by a reference model. The controller is designed by a suitable combination of differential flatness and second order sliding mode technique, which use the equivalent to the Huygen's centre of oscillation representing the flat output and the finite differential parameterisation approach approximating to the rotation angle. Simulation results demonstrate the effectiveness of the proposed controller.